A comparative study of synthetic and natural coagulants for silver nanoparticles removal from wastewater. Issue 40 (26th August 2016) - Ahmed, Toqeer; Bhatti, Zulfiqar Ahmad; Maqbool, Farhana; Mahmood, Qaisar; Faridullah,; Qayyum, Sadia; Mushtaq, Nighat
Abstract: Use of silver nanoparticles is increasing in different packaging material as disinfectant to protect food and pharmaceutical products. Its use has raised the contamination risk of fresh water and human exposure can cause serious problems. The coagulation/flocculation process can be an attractive option for silver nanoparticles removal at small-scale treatment just after its use. Four coagulants, aluminum sulfate, ferric chloride, Ocimum basilicum, and Hibiscus esculentus (synthetic and natural) were applied. For coagulation/flocculation activity, a series of jar test experiments were conducted to treat silver nanoparticles at concentration of 1 mg L −1 from wastewater. H . esculentus efficiently removed silver nanoparticles (98.7%) from aqueous solution at a dose of 150 mg L −1, whereas at same coagulant dose, ferric chloride, O . basilicum, and aluminum sulfate successfully removed silver nanoparticles at 96, 69, and 50%, respectively. No broad change in pH was observed and it remained between 6.5 and 7.5 during all the experiments at room temperature.